EFEK PEMBERIAN EKSTRAK RUMPUT KEBAR (Biophytum petersianum Klotzsch) TERHADAP JUMLAH SEL LEYDIG MENCIT (Mus musculus) JANTAN YANG DIPAPAR 2,3,7,8-TETRACHLORODIBENZO-P-DIOXIN - Nursadida, Milla; Plumeriastuti, Hani; Dhamayanti, Yeni; Widjiati, Widjiati; Luqman, Epy Muhammad; Arimbi, Arimbi (Universitas Airlangga, 2019)
This study was aim to examine the effect of kebar grass extract (Biophytum petersianum Klotzsch) to against number leydig cells of mice (Mus musculus) by exposed 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD). Twenty five male mice (Mus musculus) 4 months with avarage body weight 20 g were used. These animals were divided into five groups (K(-), K(+), P1, P2 and P3). K(-) was treated with placebo, K(+) was treated by exposed TCCD single dose injection intaperitoneal 7µg/KgBw, P1 was treated by exposed TCCD single dose injection intaperitoneal 7µg/KgBw and kebar grass extract 0,045 mg/g Bw/day P2 was treated by exposed TCCD single dose injection intaperitoneal 7µg/KgBw and kebar grass extract 0,080 mg/g Bw/day, P3 was treated by exposed TCCD single dose injection intaperitoneal 7µg/KgBw and kebar grass extract 1,350 mg/g Bw/day. This research has been conducted for 53 days. The data were compared using ANOVA and Duncan test by SPSS 22.4 for windows. The result showed that Kebar Grass Extract in all of groups can prevent the damage of leydig cells in testis that exposed by TCCD significantly (p<0,05) and kebar grass extract 0,135 mg/kgBw/day can increase amount of leydig cells maximaly.